Andrés Febrés, linguista esule in Sardegna (1783 ca – 1790). - PES, EMANUELE; PAYÀS, GERTRUDIS (Scripta, 2021)
After his arrival in Sardinia in the first half of 80’s decade, the expatriated Jesuit Andrés Febrés (Manresa, 1732 - Cagliari, 1790) seems to rediscover the linguistic interests he had already expressed with the Arte de la lengua general del reyno de Chile (Lima, 1765). In the island, hiding from Papal and Spanish agents and operating under the name of Bonifacio d’Olmi, engaged in a clandestine printing activity against the suppression of the Company, he conceived a language planning project of the Sardinian language, that included a grammar of Sardinian language varieties and at least one work in verses on which to experiment his orthographic, lexical and morphological innovations. The project largely halted as the ruling authorities in the island refused the printing permission for the grammar. Only a few handwritten pages of the grammar at the moment are known. Our purpose is to describe the outlines of Febrés’ attempt.